2004
DOI: 10.1038/modpathol.3800128
|View full text |Cite
|
Sign up to set email alerts
|

Mature B-cell acute lymphoblastic leukemia with t(9;11) translocation: a distinct subset of B-cell acute lymphoblastic leukemia

Abstract: Mature B-cell acute lymphoblastic leukemia (ALL) is typically associated with the FAB-L3 morphology and rearrangement of the MYC gene, features characteristic of the leukemic phase of Burkitt's lymphoma. However, the term 'mature' has also been used to describe other rare cases of B-ALL with light-chain surface immunoglobulin expression. In contrast, infantile B-cell ALL is generally characterized by rearrangement of the MLL gene, an immature pro-B-cell phenotype, and CD10 negativity. We describe two unusual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The only exception that we encountered was an infant suffering from a mature B-AL with FAB L1 morphology and a MLL/AF9 aberration (38). Whether the heterogeneous CD10 expression in this instance reflects an irregular differentiation of the MLL-rearranged cell population or whether only the CD10À blast cells carried the MLL rearrangement was not yet further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…The only exception that we encountered was an infant suffering from a mature B-AL with FAB L1 morphology and a MLL/AF9 aberration (38). Whether the heterogeneous CD10 expression in this instance reflects an irregular differentiation of the MLL-rearranged cell population or whether only the CD10À blast cells carried the MLL rearrangement was not yet further investigated.…”
Section: Discussionmentioning
confidence: 93%
“…1 A subgroup of Ph þ -CML mimics ET or PMF by presenting with marked thrombocytosis or myelofibrosis (MF), but only single cases with concomitant Ph þ -CML and Ph À -CMPD were reported so far. [2][3][4][5] Recently, our group Inami et al, Krämer et al, and Bornhäuser et al [2][3][4][5] simultaneously reported on four well-documented cases with concurrent JAK2 V617F and BCR-ABL translocation ( Table 1). The tyrosine kinase abnormalities appeared to affect independent subclones because imatinib mesylate (IM) treatment induced Ph þ -CML remission whereas the JAK2 V617F clone either persisted or became clinically manifest as PMF [2][3][4] or PV.…”
mentioning
confidence: 99%
“…3 Among the cases of mature B-ALL without FAB-L3 morphology and MYC rearrangement reported in children, very few present MLL gene rearrangements and especially the t(9;11) translocation. 2,4,5 We here describe an additional series of five cases of such childhood mature B-ALL with MLL rearrangement, four with the t(9;11) translocation and one with the t(10;11) translocation, and focus on their common clinical and biological characteristics.…”
mentioning
confidence: 99%
See 2 more Smart Citations